2019
DOI: 10.1002/anie.201900659
|View full text |Cite
|
Sign up to set email alerts
|

Forming Benzylic Iodides via a Nickel Catalyzed Diastereoselective Dearomative Carboiodination Reaction of Indoles

Abstract: Ad iastereoselective dearomative carboiodination reaction is reported. We report an ovel metal-catalyzed approach to install reactive secondary benzylic iodides. Utilizing the unique reactivity of nickel, we have expanded the carboiodination reaction to non-activated aromatic double bonds forming ap reviously unattainable class of iodides.W e also report ab roadly applicable method to avoid the use of ametallic reducing agent by utilizing an alkylphosphite as the ligand. The reaction is thought to proceed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…[101][102] In this process, an ickelÀcarbon bond is converted into aC ÀHb ond to release the product via protonation. This investigation constitutes the first example of an ickel-catalyzed asymmetric reductiveH eck cyclization.R ecently,L autens [120] reported ad earomative carboiodination reactiont oi nstall reactives econdary benzylic iodides (Scheme54B). The authors proposed that this reaction proceeds by the meanso fa syn intramolecular carbonickelation across a2 -substituted indole with subsequentd iastereoretentive reductive elimination of the carbon-iodine bond to afford fused isoindolinoneindoline rings.…”
Section: Ni-catalyzed Cyclization Via Dearomatization/heck Reactionmentioning
confidence: 99%
“…[101][102] In this process, an ickelÀcarbon bond is converted into aC ÀHb ond to release the product via protonation. This investigation constitutes the first example of an ickel-catalyzed asymmetric reductiveH eck cyclization.R ecently,L autens [120] reported ad earomative carboiodination reactiont oi nstall reactives econdary benzylic iodides (Scheme54B). The authors proposed that this reaction proceeds by the meanso fa syn intramolecular carbonickelation across a2 -substituted indole with subsequentd iastereoretentive reductive elimination of the carbon-iodine bond to afford fused isoindolinoneindoline rings.…”
Section: Ni-catalyzed Cyclization Via Dearomatization/heck Reactionmentioning
confidence: 99%
“…The authors also demonstrated further transformation of the polycyclic alkyl iodide via nucleophilic attack, elimination, oxidation, reduction, and copper catalyzed cross coupling reactions (Scheme 17). [33] In the same year, Lautens and group also developed a diastereoselective Ni-catalyzed intramolecular carboiodination protocol for the synthesis of anti-dihydroquinolones (DHIQs) and tetrahydroquinolines. The authors observed an interesting phenomenon while relating to the previously reported Pd-catalyzed synthesis of DHIQs, opposite diastereomers were obtained.…”
Section: Ni-catalyzed 12-difunctionalizationsmentioning
confidence: 99%
“…In 2019, the Lautens group reported an atom-economical racemic dearomative carboiodination (Scheme 24). 29 Interestingly, triethyl phosphite was sufficient to reduce the nickel precatalyst to the proposed active nickel(0) species, avoiding the need for metal reducing agents. The chiral benzylic iodides 60 were accessed in good to excellent yields and are an excellent handle for future transformations.…”
Section: Short Review Syn Thesis Scheme 21 B 2 Pin 2 Activation Versumentioning
confidence: 99%